2005
DOI: 10.1002/adma.200400879
|View full text |Cite
|
Sign up to set email alerts
|

Electron and Hole Dynamics on Isolated Chains of a Solution‐Processable Poly(thienylenevinylene) Derivative in Dilute Solution

Abstract: Poly(thienylenevinylene)s (PTVs) are p-conjugated polymers with great potential for use in electronic devices. In thin films, they have been shown to be good p-type conductors (positive charge mobility ca. 10 ±3 cm 2 V ±1 s ±1 ) but no n-type conduction has been reported. In order to investigate the mobility and dynamics of the charge carriers on PTVs at the molecular level, we used pulses of ionizing radiation to generate charges on PTV molecules in dilute solution, i.e., isolated from intermolecular interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…Since this effective mass is comparable to the effective mass for charges in inorganic semiconductors, the mobility of charge carriers along a perfectly ordered polymer chain is expected to be in the same order of magnitude as the mobility found for inorganic semiconductors, i.e., in the order of 1000 cm 2 /V s. 11 Indeed a value of 600 cm 2 /V s has been found for the mobility of holes along isolated ladder-type poly͑paraphenylene͒ chains in dilute solution by time-resolved microwave conductivity ͑TRMC͒ measurements. 12 However, the values found for the device mobility in conjugated polymers, range from 10 −7 -10 −2 cm 2 / V s, for derivatives of poly͑para-phenylenvinylene͒, poly͑thienylene-vinylene͒, poly͑thiophene͒, and ladder-type poly͑para-phenylene͒. 4,[13][14][15] These values are several orders of magnitude lower than expected on the basis of the arguments above.…”
Section: Introductionmentioning
confidence: 44%
See 3 more Smart Citations
“…Since this effective mass is comparable to the effective mass for charges in inorganic semiconductors, the mobility of charge carriers along a perfectly ordered polymer chain is expected to be in the same order of magnitude as the mobility found for inorganic semiconductors, i.e., in the order of 1000 cm 2 /V s. 11 Indeed a value of 600 cm 2 /V s has been found for the mobility of holes along isolated ladder-type poly͑paraphenylene͒ chains in dilute solution by time-resolved microwave conductivity ͑TRMC͒ measurements. 12 However, the values found for the device mobility in conjugated polymers, range from 10 −7 -10 −2 cm 2 / V s, for derivatives of poly͑para-phenylenvinylene͒, poly͑thienylene-vinylene͒, poly͑thiophene͒, and ladder-type poly͑para-phenylene͒. 4,[13][14][15] These values are several orders of magnitude lower than expected on the basis of the arguments above.…”
Section: Introductionmentioning
confidence: 44%
“…Therefore, the intrachain mobility of charges along isolated polymer chains is monitored in TRMC measurements on dilute solutions. 12,17,33,34 Since the chain-length dependence for the real mobility observed for the ladder-type polymer in solid samples is the same as the chain-length dependence observed for isolated ladder-type polymer chains, we conclude that the intrachain motion of charges is monitored in the experiments on solid samples described here.…”
Section: Lower Limit To the Complex Mobilitymentioning
confidence: 71%
See 2 more Smart Citations
“…PR-TRMC measurements have been performed for a variety of conjugated polymers and it has been found that the mobility of charges along isolated conjugated polymer chains depends strongly on the structure of the backbone. [16][17][18][19] In order to interpret and exploit the experimental data available from the measurements mentioned above it is essential to have a detailed theoretical framework describing charge transport along molecular wires. [20] The elementary processes in charge transport along conjugated polymers are similar to two-centre charge transfer reactions [21] where the efficiency of transfer depends on the energy difference and the electronic coupling (charge transfer integral) between the sites involved.…”
mentioning
confidence: 99%